A multi-center prevalence study and randomized controlled parallel-group pragmatic trial to compare the effectiveness of standardized skin care regimens on skin health in nursing home residents: A study protocol. Issue 2 (February 2015) - Kottner, Jan; Hahnel, Elisabeth; Trojahn, Carina; Stroux, Andrea; Dobos, Gabor; Lichterfeld, Andrea; Richter, Claudia; Blume-Peytavi, Ulrike
Abstract: Background: Aged long-term residents suffer from a wide range of skin problems. Dry skin associated with severe pruritus, scratching and inflammation is the most prevalent, but exact figures are lacking. Maintaining skin and tissue health as well as enhancing the quality of life are major goals in institutional long-term care. Using mild and moisturizing skin care products is considered to improve the skin barrier and to reduce adverse events. However, the available evidence supporting particular skin care approaches is limited. Objective: This study aims at answering two general questions: (1) What is the prevalence of skin conditions and skin diseases in aged nursing home residents and how are they associated with general person and health related characteristics? (2) Does a structured skin care regimen improve the skin health of aged nursing home residents? Design and methods: Using a random sample of all nursing homes of the state of Berlin, residents of seven institutions will undergo nursing, medical, and dermatological assessments. Biophysical skin parameters like transepidermal water loss or skin surface pH will be measured. Residents with dry skin will be included in a three arm randomized pragmatic trial investigating the effectiveness of two standardized skin care regimens compared to usual care. The primary outcome will be the Overall Dry Skin score. The follow-up period will be two months. Settings: Institutional long-term care facilities in Berlin, Germany. Participants: Long-term care residents being 65+ years who gave their informed consent. Sample size and statistical methods: Due to the explorative nature of this study a formal sample size analysis is not possible. The expected sample size in the first part of the study is considered sufficiently large ( n  = 280) to obtain precise point estimates. It is planned to allocate n  = 50 eligible nursing home residents in a 1:1:1 ratio per group in the intervention part. The detectable mean difference using these group sizes would be 0.32 between groups. Depending on the level of measurement variables will be described using absolute and relative frequencies, means, medians, and associated spread estimates. Possible bi- and multivariable associations will be analyzed. The primary outcome of dry skin will be described by mean differences and one-way ANOVA analysis with post-hoc pairwise two-sample t -tests. Results: The study started in September 2014. The results are expected in July 2015. Trial registration: The study is registered at https://clinicaltrials.gov/ct2/show/NCT02216526 .